AN ANYLSIS OF COMMISSIVE SPEECH ACT IN “INSIDE OUT 2” MOVIE - Wuri Wiyantari; Yasmika Baihaqi; Refai; Aulia Hanifah Qomar (Journal of English Education and Entrepreneurship (JEEP), 2026)
Speech Acts are utterances spoken by people to make a statement or describe something that affects the future. Examples are promises, threats, refusals, offers, warnings. This study aims to examine the use of Commissive Speech Acts in the film "Inside Out 2" because this film is the latest film released in 2024 and of course there will be many new commissive sentences found in the film. The researcher analyzed the film using a qualitative descriptive approach. The data used is the script of the film "Inside Out 2". Data was collected through documentation and then entered into tabulation as a data collection instrument. The researcher analyzed the data by watching the film while looking for types of speech in the film script and while noting what had been found. Furthermore, this study found that the film Inside Out 2 uses the most offers as one type of commissive speech act. The identification results found 55 examples of commissive speech acts, namely promises with a total of 10 data, threats with a total of 5 data, offers with a total of 21 data, and rejections with a total of 19 data.